A Pictorial Ultrasound Essay of Gestational Trophoblastic Disease. (29th August 2019) - Cavoretto, Paolo; Cioffi, Raffaella; Mangili, Giorgia; Petrone, Micaela; Bergamini, Alice; Rabaiotti, Emanuela; Valsecchi, Luca; Candiani, Massimo; Seckl, Michael J
Abstract : Gestational trophoblastic disease (GTD) includes a wide variety of clinical and histopathologic entities that require prompt identification and definition by the integration of clinical, laboratory, and imaging data. Recently, the role of grayscale ultrasound and spectral and power/color Doppler techniques has become pivotal in the diagnosis, staging, and management of GTD, thanks to both technical improvements and the growing expertise of dedicated operators. The aim of this essay is to summarize the most recent data on the ultrasound and Doppler findings of GTD and to provide a pictorial overview, including useful prognostic and therapeutic implications for clinical practice.